Effects of ω‐3 Polyunsaturated Fatty Acids on the Homeostasis of CD4+ T Cells and Lung Injury in Mice With Polymicrobial Sepsis. (31st July 2015) - Chang, Yu‐Fan; Hou, Yu‐Chen; Pai, Man‐Hui; Yeh, Sung‐Ling; Liu, Jun‐Jen
Abstract : Background: Sepsis is a common cause of death in critically ill patients. An overwhelming inflammatory response and imbalance of helper T (Th) cells and regulatory T (Treg) cells are thought to be involved in the progression of sepsis. ω‐3 Polyunsaturated fatty acids (PUFAs) were found to have anti‐inflammatory and immunomodulatory properties. This study investigated the effects of ω‐3 PUFAs on the balance of Th subsets, Treg cells, and the inflammatory response in septic mice. Methods : Mice were randomly assigned to soybean oil (SO) and fish oil (FO) groups. The 2 groups received an identical nutrient distribution except for the sources of the fat. The SO group was fed soybean oil, while part of the soybean oil was replaced by fish oil in the FO group. The FO group had an ω‐6/ω‐3 PUFA ratio of 2:1. After feeding the diets for 3 weeks, sepsis was induced by cecal ligation and puncture (CLP), and mice were sacrificed on days 0, 1, and 3. Results : Compared with the SO group, the FO group had lower inflammatory mediator levels in the plasma and peritoneal lavage fluid after CLP. Also, the FO group had lower Th1, Th2, and Th17 percentages and a higher Th1/Th2 ratio in blood. In lung tissues, neutrophil infiltration was reduced, whereas peroxisome proliferator–activated receptor γ expression was upregulated. Conclusions : A fish oil diet with an ω‐6/ω‐3 PUFA ratio of 2:1 may elicit more balanced Th polarization, alleviate inflammatory responses, and attenuate lung injury in CLP‐induced sepsis.